ANALISIS EFEKTIVITAS EXPO DAN OPEN HOUSE SERTA MINAT CALON SISWA INDONESIA DAN ASING PADA ENGLISH FIRST (EF) MALANG - Jusuf, Michelle Nikita (LP2M Institut Teknologi dan Bisnis Asia Malang, 2017)
At this time, it is known that in the era of globalization people are required to have such a useful provision like the foreign language skills such as English. Many foreign language education institutions also have been established in Indonesia as well as in Malang for example English First (EF), The British Institute (TBI), Institute for Language and Education Professionals LIA (LBPP LIA). Therefore, many language institutions that hold promotions in attracting students and one of them is English First (EF). There are two research problem: First, how is the differences in the effectiveness of the expo and open house to increase the number of students at the EF. Second, how is the differences in the effectiveness of expo and open house on the interests of prospective Indonesian and foreign students at EF. As this study used quantitative methods. In this research expo looks much more effective at getting students while held this event compared to the open house. In the expo can also be obtained advantages that could be closer to prospective customers and get a better response compared with the approach using the email or telephone. Effectiveness of the expo and open house at the interests of prospective Indonesian students and foreign students at the EF did not have a significant difference. In this case means that the two candidates both Indonesian and foreign students also have a passion for learning in EF.